A Synopsis of US Consumer Perception of Genetically Modified (Biotech) Crops - Edward A. Evans; Fredy H. Ballen (EDIS)
Over the last few decades, the use of modern tools of molecular biology has made it possible to discover, isolate, and introduce several important agricultural traits in cultivated crops. Such improvements are usually accomplished by the technique known as genetic engineering, also known as genetic modification. The aim of this article is to provide an update on recent developments with respect to GM food crops, as well as an assessment of US public opinion with regards to GM foods in general. A successful case of how a US-grown GM crop gained acceptance in one of the strictest fruit importing countries is presented. This 8-page fact sheet was written by Edward A. Evans and Fredy H. Ballen and published by the UF Department of Food and Resource Economics, June 2013.